The Effect Of Inflation And The Amount Of Money Circulation On Return On Asset (Roa) In Sharia Commercial Banks Period 2011-2019 - ishak ishak; arbanur rasyid; abdul nasser hasibuan; sulaiman efendi (Journal Of Sharia Banking, 2020)
The background of the problem in this study is the variable Return on Assets (ROA) in 2011-2019 at Islamic Commercial Banks. This fluctuating ROA is influenced by external factors such as inflation and the money supply. So that the formulation of the problem in this study is whether the inflation in circulation has an effect on ROA, whether the money supply affects ROA, and whether inflation and the money supply together have an effect on ROA. This study aims to determine the effect of inflation and the money supply on ROA in Islamic Commercial Banks for the period 2011-2019. This research is a quantitative research. The sample in this study used a saturated sampling technique. Using all of the population as a sample, we get 32 financial reports. The data analysis technique used time series from 2011 to 2019. Data processing used the SPSS version 22 application. The data analysis techniques used were statistical tests, classical assumptions, descriptive, normality test, multicollinearity test, heteroscedastical test, autocoleration test, hypothesis testing, multiple linear regression analysis, test the coefficient of determination. The results of the research (t test) show that the inflation variable has no effect on ROA and the money supply variable has a negative effect on ROA. Meanwhile, simultaneously (Test F) shows that the inflation variable and the money supply have a simultaneous effect on ROA. The datermination test (R2) in this study was 44,4% which was influenced by the variables in this study, while 55,6% was influenced by other variables that the researcher did not include in this study.